2009
DOI: 10.1002/esp.1877
|View full text |Cite
|
Sign up to set email alerts
|

Cobble cam: grain‐size measurements of sand to boulder from digital photographs and autocorrelation analyses

Abstract: A new application of the autocorrelation grain size analysis technique for mixed to coarse sediment settings has been investigated. Photographs of sand-to boulder-sized sediment along the Elwha River delta beach were taken from approximately 1·2 m above the ground surface, and detailed grain size measurements were made from 32 of these sites for calibration and validation. Digital photographs were found to provide accurate estimates of the long and intermediate axes of the surface sediment (r 2 > 0·98), but po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 24 publications
5
82
0
Order By: Relevance
“…error: Warrick et al 2009;Buscombe et al 2010;Buscombe and Rubin 2012;Buscombe 2013) estimates of grain size. This approach has the potential to offer unparalleled spatial or temporal resolution using relatively simple, completely automated analysis procedures.…”
Section: Variation In Nearshore Bed-sediment Grain Sizementioning
confidence: 98%
See 2 more Smart Citations
“…error: Warrick et al 2009;Buscombe et al 2010;Buscombe and Rubin 2012;Buscombe 2013) estimates of grain size. This approach has the potential to offer unparalleled spatial or temporal resolution using relatively simple, completely automated analysis procedures.…”
Section: Variation In Nearshore Bed-sediment Grain Sizementioning
confidence: 98%
“…These methods have proved to be successful in a number of sedimentary environments, with a typical error of less than 20% (Rubin et al 2007;Barnard et al 2007;Warrick et al 2009;Buscombe 2013). The method of Buscombe (2013) estimates the grain size distribution using spectral analysis on the entire image, by means of the global wavelet power spectrum that quantifies the variance contributions of grain-scale wavelengths within the image.…”
Section: Grain Sizementioning
confidence: 99%
See 1 more Smart Citation
“…In ground-based photography (Rubin, 2004;Warrick et al, 2009) and airborne photography (Carbonneau et al, 2004(Carbonneau et al, , 2005Dugdale et al, 2010), relationships were found between grain-size properties and the pixel properties. These properties, such as pixel brightness, are measured using approaches based on spatial statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Images with an unknown grain-size distribution are analyzed comparing them with autocorrelation curves that are representative of a certain sediment grain size. This method used as well by Warrick et al (2009) can be applied to a large range of grain sizes. The second approach based on spatial statistics consists in measuring the local semi-variance, which is a function of the difference in brightness and the distance between these pixels (Carbonneau et al, 2004).…”
Section: Introductionmentioning
confidence: 99%